Strategic Planning of Information Systems and Technology at a Product Label Printing Company Using the Ward & Peppard Method to Improve Operational Efficiency - Widodo, Triady; Suryani, Erma (Journal Research of Social Science, Economics, and Management, 2026)
CV Master Grafix, a small-to-medium enterprise (SME) engaged in product label printing, faces various operational challenges due to the dominance of manual processes in key business activities such as color data management, design approval, raw material procurement, and employee performance evaluation. These inefficiencies lead to service delays and decreased competitiveness in responding to the dynamic demands of B2B customers. This research aims to develop a strategic Information Systems and Information Technology (IS/IT) plan to improve the company’s operational efficiency. This study adopts a qualitative descriptive approach using a case study method and applies the Ward and Peppard framework to formulate the IS/IT strategy. Data will be collected through observation, interviews, questionnaires, and document analysis. Strategic evaluations will be conducted using approaches such as Value Chain, SWOT, Gap Analysis, Critical Success Factors (CSF), and the McFarlan Strategic Grid. Meanwhile, technology initiative priorities will be determined using the Analytic Network Process (ANP) method based on the BOCR dimensions (Benefit, Opportunity, Cost, Risk). The outcome of this research is a strategic IS/IT planning document that includes an information technology strategy, an information systems business strategy, and an IS/IT management strategy, along with a prioritized portfolio of applications. This plan is intended to serve as a foundation for developing technology solutions that enhance operational efficiency and strengthen the competitiveness of CV Master Grafix in the B2B printing industry